Communication Presentation of Indonesian Identity Figures at the Ramayana Ballet at Prambanan - Robby Hidajat; Pujiyanto Pujiyanto; EW Suprihatin; DP. Muhammad Affaf Hasiymy; Surasak Jamnongsarn (PERSPEKTIF, 2022)
This study focuses on the performing arts of tourism by examining the identity of performing arts that communicate local culture. Remembering the identity of a country becomes very quickly and easily captured through the performing arts of tourism. This article examines the identity of performing arts that tell the story of the Ramayana, which is characterized by Indonesia. In this communication process, there are two interactive paths, namely from the side of the performing arts as a carrier of information, and the audience or tourists who receive information. The process of interaction that is conveyed and received, is identity and culture. Thus, the interaction that occurs, can produce imaging through aesthetic transmission. In order to approach this problem, non-verbal communication theory is used as a reference. The data were collected through observation at the Ramayana tourist show center at Pangung open Prambanan. The data were analyzed through non-verbal communication theory aimed at the Yogyakarta style Ramayana ballet performance in the Hanoman Obong story as a local Indonesian cultural identity. Hanoman is an icon of the struggle that contains the ideology of heroism.